A quick and effective trait-based protocol for selecting appropriate native plant species for the reforestation of degraded tropical mines - Xu, Changbin; Zhang, Hui; Yang, Huai; Chen, Cui; Wang, Chen (Frontiers in Plant Science, 2024)
A critical issue in tropical forests is that anthropogenic deforestation (i.e., mining) degrades the integrity of its ecosystem. Reforestation with appropriate native plant species helps to alleviate these detrimental impacts. A protocol to select appropriate plant species for this purpose currently lacks efficacy and timeliness. We provided a trait-based protocol to quickly and effectively select native plant species for mining reforestation. A 0.2 km 2 of Baopoling (BPL) at Hainan Island, China, was used as a during reforestation of tropical mining areas.